2001: Argentine narrative in the new millennium - Blejmar, J; Bollig, B (Cambridge University Press, 2024)
The Argentine crisis of 2001 saw economic collapse, social unrest, and police repression. But if it caused a political and economic fracture with apocalyptic overtones, in literature – and in prose fiction, specifically – it did not mean a complete break with the past nor an eruption of the new, but instead the return or reformulation of the old. Despite everything, the 2000s was a period of productivity and global acclaim for Argentina’s writers. Certain activist uses of literature and its insertion in other areas of social praxis coexisted with a search for a personal voice, namely autofictions, writings of the self, and stories of everyday life. This chapter structures a reading of the literature of the 2000s around three key topics that emerge from this conjuncture: an aesthetic of recycling; an aesthetic of haunting; and the presence of a reinvigorated feminist gaze. After a period of scepticism about the role of literature in social change, these trends sparked a renewal of interest in the activist uses of fiction. At the same time, other writers made abject characters the protagonists of their stories and agitated for a literature that strives to be both autonomous and political at the same time.